AN OVERVIEW OF EMERGING ADULT ADJUSTMENT IN FACING THE TRANSITION OF PARENTAL MARITAL STATUS - Kristianti Farida; Mary Philia Elisabeth (Faculty of Psychology, Diponegoro University, 2025)
Divorce is an event that occurs in a family that will affect all aspects of the family's life, both the husband and wife and the children of their marriage. In this situation, the ability is needed to adapt to the situation at hand. Apart from that, divorce is often followed by remarriage, this event is often called a second loss event because the problem of marital status transition becomes more complex and family reorganization occurs. This research uses a qualitative research design using an interpretive phenomenological paradigm. The aim of this research is to describe the adjustment process of emerging adults in facing the transition in their parents' marital status. Three themes emerged from this research, namely barriers to adjusting to the transition to parental marital status, support for adjusting to the transition to parental marital status, and the impact resulting from the transition to parental marital status.